PCNA and Ki67 expression in breast carcinoma: correlations with clinical and biological variables. Issue 5 (May 1992) - Leonardi, E; Girlando, S; Serio, G; Mauri, F A; Perrone, G; Scampini, S; Dalla Palma, P; Barbareschi, M
Abstract : AIMS: To investigate the expression of two cell cycle related antigens (proliferating cell nuclear antigen (PCNA) and Ki67 related antigen) in a series of breast cancers; and the possible correlations between the PCNA and Ki67 labelling indexes (PCNA-LI and Ki67-LI) and their associations with other biological and clinicopathological variables. METHODS: Ninety six ductal and 10 lobular carcinoma specimens were investigated. Samples were fixed in formalin and in Methacarnoy for localisation of PCNA. Ki67 was immunostained on frozen sections. The PCNA-LI and Ki67-LI were evaluated in relation to tumour size, mitotic count, histological grade, nodal state as well as receptor content and altered expression of the p53 gene. RESULTS: PCNA-LI did not correlate with Ki67-LI, nor was it associated with any other variable examined. A high KI67-LI (above the median value of 13.5) was associated with high grade and mitotic count, negative receptor content, and altered expression of the p53 gene, but not with other variables. CONCLUSIONS: The PCNA-LI does not seem to be a substitute for the Ki67-LI in evaluating the growth fraction in breast cancer.